La « bonne mesure » de l’expression de la féminité et de la masculinité au sein de l’institution scolaire en Martinique(2015-2016) - Michel Tondellier (Amnis)
This article addresses little studied form of power relations, which are observed in educational communities : controlling student through uniform policies. The written traces of these power relations sometimes define with very much precision the dress code to be respected within the schools. These prohibitions inform us about the gender stereotypes that animate educational communities that distinguish "good" from "bad" students by encouraging adherence to very measured forms of masculinity and femininity. Then we will try, on the one hand to clarify the mechanisms of exclusion of non-compliant students and, on the other hand, to illuminate the elements contributing to the socio-historical anchoring of these forms of accomplice, subordinate or marginalized masculinities and femininity. What are the historical, economic, social and cultural factors that are favoring the creation of a gendered social structure specific to the French West Indies ?